2015
DOI: 10.1111/jgs.13321
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sleep‐Disordered Breathing, Nocturnal Hypoxemia, and Subsequent Cognitive Decline in Older Community‐Dwelling Men: The Osteoporotic Fractures in Men Sleep Study

Abstract: OBJECTIVES Sleep-disordered breathing (SDB) is a group of disorders common among older adults, characterized by breathing pauses during sleep often accompanied by hypoxemia. Few studies have examined if SDB is associated with cognitive decline. DESIGN A population-based longitudinal study. SETTING 6 centers in the United States. PARTICIPANTS 2,636 community-dwelling older men (age 76.0 ± 5.3 years) without mild cognitive impairment, followed 3.4 ± 0.5 years. MEASUREMENTS SDB, measured by in-home polyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 49 publications
6
81
0
2
Order By: Relevance
“…Our interpretation of these results is that OSA may account for these findings. Further, OSA may play an important role in amyloid deposition, significantly increasing risk for the development of dementia as well as acceleration of cognitive decline, as has been previously demonstrated by prospective observational studies [3][4][5][6]. However, our results need to be supported by additional basic, translational, and observational studies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our interpretation of these results is that OSA may account for these findings. Further, OSA may play an important role in amyloid deposition, significantly increasing risk for the development of dementia as well as acceleration of cognitive decline, as has been previously demonstrated by prospective observational studies [3][4][5][6]. However, our results need to be supported by additional basic, translational, and observational studies.…”
Section: Discussionsupporting
confidence: 58%
“…Observational studies demonstrated that OSA is associated with slower cognitive processing speed [2], increased risk of incident dementia in older women [3], and accelerated cognitive decline in the elderly [4][5][6]. Cerebral white matter change, a risk factor for dementia, is more frequently observed in OSA [7].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed descriptive statistics are not presented in this short note, but characteristics of similar study samples can be found in previous publications. 2,3,11 After multivariable adjustment, the rate of increase in Trails B test time (decline in function) was significantly greater for those with a PLMI ≥ 30, whereas the rate of decrease in 3MS scores was smaller, but not significant, for those with a PLMI ≥ 30. The adjusted increase in Trails B test completion time over 3.4 y were 3.5, 6.3, and 8.1 sec for PLMI category of < 5, 5 to 30, and ≥ 30, respectively (P for trend = 0.02); adjusted decline in 3MS score for PLMI categories were 1.3, 0.9, and 1.0 points over 3 y, respectively (P for trend = 0.23).…”
Section: Resultsmentioning
confidence: 97%
“…11 After excluding men with significant cognitive impairment at the sleep visit (Modified Mini-Mental State examination (3MS) score < 80 or taking a medication for dementia), the current analysis In-home sleep studies were completed using unattended polysomography (Safiro, Compumedics, Inc., Melbourne, Australia), following a standardized protocol as described previously. 2 Bilateral tibialis leg movements were measured with piezoelectric sensors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation